2016
DOI: 10.1055/s-0042-108588
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative optische Kohärenztomografie bei der tiefen anterioren lamellären Keratoplastik

Abstract: Intraoperative OCT facilitates standardisation during several steps of DALK. Future prospective studies should concentrate on the safety profile of intraoperative OCT-guided DALK compared to DALK without intraoperative monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“… 13 Several observations were of the opinion that, with iOCT in DALK, the plane of canula introduction, its effect on big bubble morphology and subsequent manual dissection, and suture depth sagacity are all well executed. 14 In addition, the effect of intraocular pressures on the success of big bubble technique, 15 interface events during surgery, 16 , 17 and the added advantage of femtosecond laser in the customization of intraoperative parameters have all provided the inclusive notions for using iOCT. 18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 Several observations were of the opinion that, with iOCT in DALK, the plane of canula introduction, its effect on big bubble morphology and subsequent manual dissection, and suture depth sagacity are all well executed. 14 In addition, the effect of intraocular pressures on the success of big bubble technique, 15 interface events during surgery, 16 , 17 and the added advantage of femtosecond laser in the customization of intraoperative parameters have all provided the inclusive notions for using iOCT. 18…”
Section: Resultsmentioning
confidence: 99%
“…13 Several observations were of the opinion that, with iOCT in DALK, the plane of canula introduction, its effect on big bubble morphology and subsequent manual dissection, and suture depth sagacity are all well executed. 14 In addition, the effect of intraocular pressures on the success of big bubble technique, 15 interface events during surgery, 16,17 and the added advantage of femtosecond laser in the customization of intraoperative parameters have all provided the inclusive notions for using iOCT. 18 Under complex clinical scenarios, such as the identification of superficial fibrovascular tissue in severe limbal stem cell deficiency, iOCT helps in the discretion of abnormal tissue from normal, thus preventing excessive resection of healthy tissue.…”
Section: Cornea Refractive and Cataract Utility In Corneal Surgeriesmentioning
confidence: 99%
“…Several authors have addressed the problem and proposed variations in the technique that reduce the rate of this complication [ 47 , 48 ]. Recently, the creation of tunnels using femtosecond laser as a pretreatment for the creation of a big bubble has been proposed by Diakonis et al [ 49 ], while Siebelmann et al reported the increased safety of intraoperative use of OCT in DALK [ 50 ].…”
Section: Current Treatment Options and Managementmentioning
confidence: 99%
“…AS-OCT may help to visualize pre-Descemetal scarring in order to check patients' eligibility for DALK. The utility of intraoperative AS-OCT has been proven for analyzing whether the diseased stroma has been fully removed and whether the transplant has been well integrated into the host tissue [19,20]. In the follow-up AS-OCT again is useful to check the graft adhesion to the host's DM or to visualize DM and the anterior chamber if the view is limited due to increased light scatter caused by corneal edema ( Figure 5).…”
Section: Keratoconusmentioning
confidence: 99%